Atypical presentations of celiac disease - Celiloğlu, Can; Karabiber, Hamza; Selimoğlu, Mukadder Ayşe (The Turkish Journal of Pediatrics, 2011)
Celiac disease (CD) has a wide variety of clinical presentations; together with the "classical form", in which the intestinal symptomatology is prevalent, there are "atypical forms" with predominating extra-intestinal clinical features, and the "silent form", with no clinical symptom. The "atypical forms" of the disease are characterized by few or no gastrointestinal symptoms, and predominating extra-intestinal features such as neurologic, dermatologic, hematologic, endocrinologic, reproductive, renal, psychiatric, skeletal, and liver involvement(s). Silent presentation of CD may be identified through screening of high-risk groups. Today, it is well known that CD might account for several chronic health issues, so it is essential for healthcare professionals to have a high level of suspicion for the atypical presentations of CD.